2010
DOI: 10.1074/jbc.m110.114561
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Huntington Disease Protein in Dendritic RNA Granules

Abstract: Regulated transport and local translation of mRNA in neurons are critical for modulating synaptic strength, maintaining proper neural circuitry, and establishing long term memory. Neuronal RNA granules are ribonucleoprotein particles that serve to transport mRNA along microtubules and control local protein synthesis in response to synaptic activity. Studies suggest that neuronal RNA granules share similar structures and functions with somatic P-bodies. We recently reported that the Huntington disease protein h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 58 publications
7
77
0
Order By: Relevance
“…The relative density of the bands was determined using ImageJ software. A similar reporter assay has been used to determine the role of huntingtin in dendritic RNA granules (30) and the localization of MAP2 and CaMKII␣ mRNA into distinct ribonucleoprotein particles along dendrites of hippocampal neurons (31). Our results show that there is increased expression of GFP in the avian skeletal muscle cultures transfected with pEGFP-AChE-3Ј-UTRmut compared with those transfected with pEGFP-AChE-3Ј-UTR (Fig.…”
Section: Pum2 Issupporting
confidence: 56%
“…The relative density of the bands was determined using ImageJ software. A similar reporter assay has been used to determine the role of huntingtin in dendritic RNA granules (30) and the localization of MAP2 and CaMKII␣ mRNA into distinct ribonucleoprotein particles along dendrites of hippocampal neurons (31). Our results show that there is increased expression of GFP in the avian skeletal muscle cultures transfected with pEGFP-AChE-3Ј-UTRmut compared with those transfected with pEGFP-AChE-3Ј-UTR (Fig.…”
Section: Pum2 Issupporting
confidence: 56%
“…The data generated from our purifications expand upon our earlier studies (14,48,49) by identifying a link between Htt and translation. Both wild-type and mutant Htt co-purify with sev- eral translation-related proteins, co-fractionate with ribosomes, localize to stress granules, and inhibit translation when overexpressed in an in vitro assay.…”
Section: Discussionmentioning
confidence: 77%
“…Mutant Htt Purifications Implicate Altered RNA MetabolismWe have previously demonstrated that wild-type Htt functions with argonaute 2 (Ago2, the catalytic component of the RNAinduced silencing complex) in a post-transcriptional gene silencing pathway (14) and is also involved in RNA transport in cultured cortical neurons (48,49). The current study points to Htt function in protein synthesis through its interactions with ribosomal proteins, various translation initiation factors, and other accessory proteins.…”
Section: ϫ10mentioning
confidence: 94%
“…20,21 Rhes, a striatal-specific guanine nucleotide-binding protein, interacts preferentially with polyQ-expanded Htt and induces its sumoylation, leading to cytotoxicity. 22 Interactors of Htt include several proteins related to RNA processing; 23,24 however, their relation to the polyQ expansion has not been elucidated. Two systematic studies of the Htt interactome have been reported to date: Wanker and coworkers used yeast two-hybrid screens to describe a protein interactions network for HD.…”
Section: Resultsmentioning
confidence: 99%
“…Mutant Htt associates with Ago2 in P bodies and contributes to RNA-mediated gene silencing. 23,24 P bodies, unlike SG, are not associated with ribosome and mostly serve for storage and degradation of repressed mRNAs. P bodies contain decapping enzymes and endonucleases and may associate with components of RISC complex (argonaute, DICER).…”
Section: Discussionmentioning
confidence: 99%